Implantation and Extraction of Penetrating Electrode Arrays in Minipig Retinas - Chen, Jinghua (Transl Vis Sci Technol, 2020)
PURPOSE: This work was motivated by the goals of demonstrating methods to fabricate and implant large numbers of penetrating arrays into the retina and the feasibility of extraction. METHODS: Arrays of inactive, three-dimensional (3D) SU-8 structures were microfabricated onto 13-µm polyimide substrates. Standard vitreoretinal surgical techniques were used with an ab externo approach for subretinal implantation of arrays in 12 mini-pigs. In the first three surgeries, different post-geometries were explored, while a preferred design (128-µm tall, 30-µm diameter, 200-µm spacing) was used for the remaining nine implantations. Two arrays were extracted. Funduscopy, optical coherence tomography (OCT) and immunohistochemistry of the retinae were performed. The unoperated eyes and tissue far from implantation served as controls. A thirteenth pig was implanted with a planar array. RESULTS: Ten implant surgeries had no significant complication, and two arrays were successfully extracted. One retinal tear occurred after implantation due to too long posts in an early surgery. In “successful” cases, OCT showed close apposition of the arrays to the retina and integration of the posts, the tops of which were positioned at the junction of the inner plexiform and ganglion cells, without significant gliosis. CONCLUSIONS: These results provide a proof-of-concept that relatively large numbers of 3D posts can be implanted into, and extracted from, the retina of mini-pigs. Our surgical numbers were relatively small, especially for the extractions, and our conclusions must be viewed with that limitation. Our methods are applicable for human surgeries. TRANSLATIONAL RELEVANCE: This study provides results of implantation and extraction of relatively large numbers of 3D posts from the retina of minipig eyes. If similar technology were used in humans, a 3D array of this type should lower perceptual thresholds, provide safer long-term stimulation, and perhaps provide better perceptual outcomes.